Successful bony integration of a porous tantalum implant despite longlasting and ongoing infection: Histologic workup of an explanted shoulder prosthesis. Issue 8 (10th September 2018) - Wahl, Peter; Sprecher, Christoph M.; Brüning, Christian; Meier, Christoph; Milz, Stefan; Gautier, Emanuel; Fintan Moriarty, T
ABSTRACT: Infection associated with an implant is a complication feared in surgery, as it leads to loosening and dysfunction. This report documents an unexpected good bony integration of a porous tantalum shoulder prosthesis despite infection. A shoulder prosthesis with a porous tantalum glenoidal base plate was retrieved after 3 years of ongoing infection with Staphylococcus spp . Methyl‐methacrylate embedded sections of the retrieved glenoidal component were analyzed by optical and scanning electron beam microscopy (SEM). Bone ongrowth and ingrowth were quantified. Bone had formed at the implant surface and within the open cell structure of the porous tantalum. The bone implant contact index was 32%. The bone ingrowth or relative bone area within the open structure was 8.2%, respectively 11.9% in the outer 50% of the thickness. Due to the section thickness, bone ongrowth could best be documented in SEM. Despite long‐lasting and ongoing infection, the glenoidal base plate of the prosthesis showed good bony integration upon removal. The bone ingrowth into the porous tantalum was comparable to the values previously reported for the undersurface of retrieved proximal humerus resurfacing implants. Good integration of the implant however did not solve the problem of infection, and related morbidity. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 2924–2931, 2018.